Urodynamics for Prostate Surgery Trial; Randomised Evaluation of Assessment Methods (UPSTREAM) for diagnosis and management of bladder outlet obstruction in men: study protocol for a randomised controlled trial. Issue 1 (December 2015) - Bailey, K.; Abrams, P.; Blair, P.; Chapple, C.; Glazener, C.; Horwood, J.; Lane, J.; McGrath, J.; Noble, S.; Pickard, R.; Taylor, G.; Young, G.; et al.
Abstract Background Lower urinary tract symptoms (LUTS) comprise storage symptoms, voiding symptoms and post-voiding symptoms. Prevalence and severity of LUTS increase with age and the progressive increase in the aged population group has emphasised the importance to our society of appropriate and effective management of male LUTS. Identification of causal mechanisms is needed to optimise treatment and uroflowmetry is the simplest non-invasive test of voiding function. Invasive urodynamics can evaluate storage function and voiding function; however, there is currently insufficient evidence to support urodynamics becoming part of routine practice in the clinical evaluation of male LUTS. Design A 2-arm trial, set in urology departments of at least 26 National Health Service (NHS) hospitals in the United Kingdom (UK), randomising men with bothersome LUTS for whom surgeons would consider offering surgery, between a care pathway based on urodynamic tests with invasive multichannel cystometry and a care pathway based on non-invasive routine tests. The aim of the trial is to determine whether a care pathway not including invasive urodynamics is no worse for men in terms of symptom outcome than one in which it is included, at 18 months after randomisation. This primary clinical outcome will be measured with the International Prostate Symptom Score (IPSS). We will also establish whether inclusion of invasive urodynamics reduces rates of bladder outlet surgery as a main secondary outcome. Discussion The general population has an increased life-expectancy and, as men get older, their prostates enlarge and potentially cause benign prostatic obstruction (BPO) which often requires surgery. Furthermore, voiding symptoms become increasingly prevalent, some of which may not be due to BPO. Therefore, as the population ages, more operations will be considered to relieve BPO, some of which may not actually be appropriate. Hence, there is sustained interest in the diagnostic pathway and this trial could improve the chances of an accurate diagnosis and reduce overall numbers of surgical interventions for BPO in the NHS. The morbidity, and therapy costs, of testing must be weighed against the cost saving of surgery reduction. Trial registration Controlled-trials.com -ISRCTN56164274 (confirmed registration: 8 April 2014).